Who Cares If the Teacher Has a Cat? The Impact of Affect and Interaction upon Motivation in Online Portuguese L2 Classes during the COVID-19 Pandemic - Bruno Costa; Jorge Pinto (Theory and Practice of Second Language Acquisition)
This study examined the motivational impact of affect/interaction in emergency remote teaching (ERT) Portuguese L2 classes. Participants were two groups of students from 13 countries living in Portugal (N = 16). A mixed-method paradigm was adopted, consisting of a closed questionnaire, class observations, and semi-structured interviews. Results showed a generally positive impact of the practices adopted by both teachers. Comparatively, the group whose teacher evidenced a stronger affect-based strategy presented better results in measures related to motivation to learn Portuguese (MLP), perception of the teacher/classes (PTC), perception of individual capacities (PIC) and test anxiety, regardless of learners being more critical of the lack of socialization and reticent about sharing personal information. However, the group whose teacher favored interactive tasks showed greater engagement and enjoyment/flow. Statistical tests revealed a significant positive correlation between PTC and MLP, and a negative correlation between these two and test anxiety. It is proposed that the combination of affect and interaction can compensate for the demotivating effect of lack of face-to-face contact in ERT L2 classes.